APPLICATION OF ROUND CLUB LEARNING MODEL TO IMPROVE MOTIVATION AND LEARNING OUTCOMES OF UPT SMPN 10 PINRANG STUDENTS - Herman Herman; Muh Yahya; Elpisah Elpisah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2023)
This increasingly modern era often affects students so that their learning motivation becomes faded and results in student learning outcomes not meeting the criteria for maximum school completion. Therefore, it is necessary for a teacher as a professional to overcome it, such as applying innovative and varied learning models in each subject. This study aims to improve student motivation and learning outcomes through the Round Clud learning model in class X TBSM UPT SMK Negeri 10 Pinrang. This research is a class action research so that data collection is in the form of observation methods, test methods, and documentation. The data obtained then analyzes it with analytical descriptive analysis techniques. The results showed that 1) The percentage of student learning motivation increased each cycle. Where in the first cycle it is in the low category of 40.4% and increases in cycle II with a very high category of 80%, 2) The completeness of student learning outcomes has increased every cycle. Where the average in cycle I is 67.9 and increases to 88.3 in cycle II, then in classical completion in cycle I by 30% and cycle II increases to 90%. Thus, it is concluded that the application of the Round Club learning model can increase student motivation and student learning outcomes in Indonesian history subjects for class X upt students of SMK Negeri 10 Pinrang.